Aerobic minutes and step number remain low in inpatient stroke rehabilitation - Yunyi Yan; Janice J. Eng; Stanley H. Hung; Mark T. Bayley; Krista L. Best; Louise A. Connell; Sarah J. Donkers; Sean P. Dukelow; Victor E. Ezeugwu; Marie-Hélène Milot; Brodie M. Sakakibara; Lisa Sheehy; et al. (PLoS ONE, 2025)
Objective Rehabilitation is important for regaining mobility poststroke. Clinical practice guidelines suggest a high number of repetitive stepping activities to optimize subacute recovery especially when undertaken at intensities that challenge cardiovascular fitness. However, adherence to these guidelines is unclear. The objective of this study was to quantify aerobic minutes and step number in usual care inpatient stroke rehabilitation unit physical therapy sessions across Canada and identify characteristics of participants who met guideline aerobic intensity minutes at a session midpoint in their rehabilitation. Methods To gain insight into usual care, we analyzed cross-sectional data from the usual care arm of the Walk ‘n Watch implementation trial; trial sites included Canadian rehabilitation units that were not typically involved in research studies. To be included, medically stable patients were admitted for inpatient stroke rehabilitation, and able to take > 5 steps with a maximum of one person assisting. We assessed a midpoint physical therapy session with a wrist-based heart monitor (aerobic minutes) and ankle-based step counter (step number). Means, histograms, and correlations between aerobic minutes (> 40% heart rate reserve) and steps were calculated. Results There were 166 participants (69 females, age 69 standard deviation (SD)12 years) with stroke (138 Ischemic/ 27 Hemorrhagic) included. Participants had a mean of 10(SD11) aerobic minutes and 985(SD579) steps. The relationship between step number and aerobic minutes was negligible (R2 = 0.003). More participants with ≥20 aerobic minutes in a session were male, with lower 6 Minute Walk Test distance, and have a subcortical stroke location. Conclusion The number of steps has increased, but aerobic minutes has not changed and remains extremely low compared to published reports in the past several years. Given that increasing activity levels are critical for stroke recovery, further investigation into the potential barriers to achieving targets set by guidelines is recommended. Trial registration ClinicalTrials.gov NCT04238260